ANALISIS PERPUTARAN MODAL KERJA, CURREN RATIO, DAN PERPUTARAN TOTAL ASET TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BEI - Sitorus, Rivana Eva Emeliana; Tipa, Handra (SCIENTIA JOURNAL, 2021)
This study aims to determine the effect of working capital turnover, current ratio, and total asset turnover on the profitability of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020. The data analysis method used is quantitative data analysis with technical analysis. multiple linear regression analysis. The data used is secondary data obtained by the documentation method on the financial statements on the Indonesia Stock Exchange (IDX). The total population in this study is 19 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This study uses a sampling technique with purposive sampling method so that there are 12 companies that meet the criteria. This research uses SPSS version 25 program in processing the data. The results of the t test are partially, working capital turnover and current ratio have a significant effect on company profitability. While the total asset turnover partially does not have a significant effect on the company's profitability. The results of the F test are that working capital turnover, current ratio, and total asset turnover simultaneously have a significant effect on company profitability. The results of the coefficient of determination test are 0.443, which means the percentage contribution of the variable working capital turnover, current ratio and total asset turnover is 44.3% while the remaining 55.7% is explained by other factors Keywords: Capital Turnover, Current Ratio, Profitability and Total Asset Turnover